توصيات بشأن ا ليضانع ا خطرة: لائحة تنظيمية نموذجية - United Nations (United Nations, 2009)
These recommendations have been developed in the light of technical progress, the advent of new substances and materials, the exigencies of modern transport systems and, above all, the requirement to ensure the safety of people, property and the environment. They are addressed to governments and international organisations concerned with the regulation of the transport of dangerous goods. The Model Regulations cover the classification of dangerous goods, their listing, the use, construction, testing and approval of packagings and portable tanks, as well as consignment procedures such as marking, labeling, placarding and documentation. This sixteenth revised edition contains new provisions (e.g. transport of substances which are toxic by inhalation, requirements for metal hydride storage systems, provisions for fuel cell engines, use of open cryogenic receptacles) and revised provisions.